Extended stereopsis evaluation of professional and amateur soccer players and subjects without soccer background - Paulus, Jan; Tong, Jie; Hornegger, Joachim; Schmidt, Michael; Eskofier, Björn; Michelson, Georg (Frontiers in Psychology, 2014)
Stereopsis is one of several visual depth cues. It has been evaluated for athletes of different types of sports in the past. However, most studies do not cover the full range of stereopsis performance. Therefore, we propose computer-supported stereopsis tests that provide an extended assessment and analysis of stereopsis performance including stereo acuity and response times. By providing stationary and moving stimuli they cover static and dynamic stereopsis. The proposed stereopsis tests were used to compare professional and amateur soccer players with subjects without soccer background. The soccer players could not perform significantly (p <= 0.05) superior than the subjects without soccer background. However, the soccer players showed significantly (p <= 0.01) superior choice reaction times for monocular stimuli. The results are in congruence with previous findings in literature.